2014
DOI: 10.1186/1471-2458-14-1215
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of clustering of six health-compromising behaviours in Saudi adolescents

Abstract: BackgroundClustering of multiple health-compromising behaviours is associated with an increased risk of various chronic diseases. There are few studies on patterns of clustering of multiple health-compromising behaviours in adolescents. Therefore, the aim of this study is to assess how six health-compromising behaviours, namely, low fruit consumption, high sweet consumption, less frequent tooth brushing, low physical activity, physical fighting and smoking, cluster among Saudi male adolescents.MethodsA represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 49 publications
2
38
0
Order By: Relevance
“…Previous studies employing various techniques of data analysis have also shown a similar pattern of clustering for insufficient physical activity and low fruit intake (as part of an unhealthy diet) in adolescents, thus characterizing a sedentary lifestyle. As for the first cluster, equivalent findings have been reported, especially concerning the co‐occurrence of smoking and drug use, smoking and high sugar intake, and less frequent oral and general hygiene practices …”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Previous studies employing various techniques of data analysis have also shown a similar pattern of clustering for insufficient physical activity and low fruit intake (as part of an unhealthy diet) in adolescents, thus characterizing a sedentary lifestyle. As for the first cluster, equivalent findings have been reported, especially concerning the co‐occurrence of smoking and drug use, smoking and high sugar intake, and less frequent oral and general hygiene practices …”
Section: Discussionmentioning
confidence: 63%
“…It is been documented in the literature that unfavourable behaviours tend to co‐occur in adolescents, in the so‐called problem behaviour syndrome . This theory has been expanded to include health behaviours, because many unfavourable behaviours, such as alcohol use, marijuana use, unprotected sex and driving after drinking, can be considered health‐compromising and contrary to social norms …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As public investment in infrastructure continues to decrease, private participation is required to address the existing and expanding deficit in medical services, especially for chronic cases, patient behaviour, and treatment mechanisms [35]. Despite great progress in PHC services, PPPs may be more successful in secondary healthcare services due to high demand from the population.…”
Section: Discussionmentioning
confidence: 99%
“…Political and organizational approaches to policy analysis estimate the policy itself as a decision-making process rather than focusing on health output [32]. Measuring patient behaviours and endorsing ineffective health awareness and misled ideologies in medicine were two common themes within a primarily publicly funded system [3335]. Even so, effective regulation and government support were the key elements of national health progress [36].…”
Section: Introductionmentioning
confidence: 99%